2011
DOI: 10.1111/j.1399-6576.2011.02541.x
|View full text |Cite
|
Sign up to set email alerts
|

Forces applied to the maxillary incisors by video laryngoscopes and the Macintosh laryngoscope

Abstract: All VLSs considered were safer for the patient than was the Macintosh blade in terms of the forces applied to the maxillary teeth, time, number of insertion attempts, and view achieved of the glottic arch. There is a small, but significant, difference in the time and number of insertion attempts required during laryngoscopy with the different VLSs. There was no difference in the forces applied. The geometry of the respective blades may be an important component in the ease of laryngoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
3
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 21 publications
4
36
3
2
Order By: Relevance
“…Despite this, the intubation with Glidescope TM video laryngoscopy (GVL) was remarkably easy. Glidescope TM video laryngoscopy has been shown to improve glottic view and intubation success in a number of studies [23][24][25][26][27]. One study identified GVL was 98% successful as a primary technique and GVL after failed DL was 94% successful in 2004 cases [27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite this, the intubation with Glidescope TM video laryngoscopy (GVL) was remarkably easy. Glidescope TM video laryngoscopy has been shown to improve glottic view and intubation success in a number of studies [23][24][25][26][27]. One study identified GVL was 98% successful as a primary technique and GVL after failed DL was 94% successful in 2004 cases [27].…”
Section: Discussionmentioning
confidence: 99%
“…This is because the forces applied to the maxillary incisors are significantly greater with the Macintosh blade compared with all video laryngoscopes (VLSs) [23]. One study measured the mean forces applied by trained and untrained personnel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Les résultats en termes de forces appliquées sur les incisives maxillaires lors de l'intubation sont plus éle-vés sans pour autant être significativement différents pour les laryngoscopes à lame droite par rapport à tous les VLs. Toutefois, le temps d'intubation, le nombre de tentatives et la vue glottique présentent de meilleurs résultats avec les VLs avec une différence significative [24].…”
Section: Apport Des Vidéolaryngoscopesunclassified
“…The C-MAC VLS offers even more, as it can be used as a tool for direct and indirect laryngoscopy (6). This VLS offers several beneficial options that may help in realizing a patent airway and satisfactory gas exchange during endotracheal intubation for all indications (normal and difficult airways) including: a) an improved view of the glottis (avoiding failed laryngoscopy) without the need for aligning the oral, pharyngeal and laryngeal axes (20,25,30); b) higher first attempt and overall intubation success rate; c) fast time to successful intubation; d) less frequent need of adjuncts and manoeuvers (16,17); e) least number of complications (less forces exerted on maxillary incisors and hence less dental trauma; less mucosal trauma due to the "blind" spot (6,14,21,35,65); in most cases stylets are not essential) (16,17); and e) beneficial physical characteristics such as: i) wide angle of view (6); ii) strongest lamp and brightest illumination of the oropharynx (63); iii) recording and image storage options with high number of pixels (6); iv) multimodular system which provides options to use the monitor display for other functions (fiberoptic or rigid scope); v) system that provides a wide range of interchangeable blades (reusable, disposable, Macintosh and angled blades) (6); vi) portable and lightweight system; vii) reliable airway visualisation without fogging (61); viii) that allows direct and indirect laryngoscope using the same blade (6). Videolaryngoscopy will be acceptable to clinicians for all forms of practice as it offers advantages in difficult intubations while not imposing a penalty when intubation is practiced on normal airways.…”
Section: Clinical (N Of Patients) Manikin (N Of Providers)mentioning
confidence: 99%